Development of primer sets for detection of Raspberry leaf blotch virus and Raspberry leaf mottle virus by multiplex RT-PCR - Gritsenko, D.; Kerimbek , N.; Kapytina , A.; Pozharskiy , A.; Nizamdinova , G.; Taskuzhina, A.; Kostyukova, V.; Adilbayeva , K. (Eurasian Journal of Applied Biotechnology, 2022)
More than 40 viruses and virus-like agents have been confirmed to infect Rubus species including raspberry (R. idaeus and R. occidentalis) and blackberry. The ones of most distributed viruses among cultivated raspberries are Raspberry leaf blotch virus (RLMV) and Raspberry leaf mottle virus (RLBV). The influence of these viruses on the raspberry crop yield is large and losses count in 30-50%. To detect the infected stock planting material or plants carrying infection in orchards, the sets of primer have been developed in this work. Capsid protein gene and nucleocapsid protein gene of RLMV and RLBV, respectively, were considered for design of primers. The specificity analysis confirmed absence of any off-target complementary of primers considering the nucleotide collection of NCBI. Eighty-five samples of raspberry were tested by developed primers. Four cultivars of pomological garden and one raspberry plant of wild population were positive for RLMV and RLBV, respectively. The sequencing analysis of RLMV CP and RLBV NP revealed, that homology with isolates from Bosnia and Herzegovina is higher compared to other isolates in NCBI.